Protective factors for older suicide attempters: Finding reasons and experiences to live. Issue 7 (2nd July 2020) - Deuter, Kate; Procter, Nicholas; Evans, David
Abstract: This paper describes the nature and scope of protective factors that give older people reasons and experiences to live following a suicide attempt. In order to understand more about what protective factors influenced them, we conducted a multiple-case study of seven older people who attempted suicide. The main category from the within-case analysis was the self. Between-case analysis identified four main categories: interpersonal relationships, meaningful activities and interests, community engagement, and involvement of mental health services staff. These findings offer valuable insight into the meanings behind the reasons and experiences that promote survival of older people following a suicide attempt.